Interacting Effects of Cell Size and Temperature on Gene Expression, Growth, Development and Swimming Performance in Larval Zebrafish - van de Pol, Iris Louise Eleonora; Hermaniuk, Adam; Verberk, Wilhelmus Cornelis Egbertus Petrus (Frontiers in Physiology, 2021)
Cell size may be important in understanding the thermal biology of ectotherms, as the regulation and consequences of cell size appear to be temperature dependent. Using a recently developed model system of triploid zebrafish (which have around 1.5-fold larger cells than their diploid counterparts) we examine the effects of cell size on gene expression, growth, development and swimming performance in zebrafish larvae at different temperatures. Both temperature and ploidy affected the expression of genes related to metabolic processes (citrate synthase and lactate dehydrogenase), growth and swimming performance. Temperature also increased development rate, but there was no effect of ploidy level. We did find interactive effects between ploidy and temperature for gene expression, body size and swimming performance, confirming that the consequences of cell size are temperature dependent. Triploids with larger cells performed best at cool conditions, while diploids performed better at warmer conditions. These results suggest different selection pressures on ectotherms and their cell size in cold and warm habitats.